Feasibility analysis of off-grid hybrid energy system for rural electrification in Northern Ghana. Issue 1 (1st January 2021) - Awopone, Albert K.
Abstract: This study examines the feasibility of a stand-alone photovoltaic, diesel generator and battery storage hybrid power system for the electrification of off-grid rural areas in northern Ghana. The HOMER software package was used for simulation analysis. Five optimization scenarios considered feasible by HOMER were evaluated. The evaluation criteria include net present cost (NPC), cost of energy (COE) and emissions. The results indicate that PV/diesel/battery storage hybrid system is the most feasible, optimized, cost-effective and environmentally friendly system among the systems considered. This system has a Cost of Energy (COE) of 0.399 /kWh and an NPC of 296, 552. Although this COE is approximately three times the current energy cost in Ghana, sensitivity analysis shows that changing certain parameters such as fuel costs, and capital subsidies can reduce COE. This shows that if policymakers create the necessary investment environment, such projects can be a viable alternative to rural electrification.